Hall Effect on MHD Transient Flow Past an Impulsively Started Infinite Horizontal Porous Plate in a Rotating System - B. Prabhakar Reddy (International Journal of Applied Mechanics and Engineering, 2018)
In this paper, the effect of Hall current on an unsteady MHD transient three dimensional flow of an electrically conducting viscous incompressible fluid past an impulsively started infinite horizontal porous plate relative to a rotating system has been studied. It is assumed that the entire system rotates with a constant angular velocity about the normal to the plate and a uniform magnetic field is applied along the normal to the plate and directed into the fluid region. The magnetic Reynolds number is assumed to be so small that the induced magnetic field can be neglected. The expressions for the primary and secondary fields and shearing stress at the plate due to primary and secondary velocity fields are obtained in a non-dimensional form. The non-dimensional governing equations of the flow are solved by using the Galerkin FEM. The effects of the physical parameters, such as the Hartmann number (M), rotation parameter (Ω), porosity parameter ( K ) and Hall parameter (m) on primary and secondary velocities and shearing stresses τ x and τ y due to primary and secondary velocities are discussed through graphs and tables, and results are physically interpreted.